Adaptabilidad de cinco variedades de frijol (Phaseolus vulgaris), en la finca Angamarca la vieja del cantón Pangua, provincia de Cotopaxi año 2013 - Cornelio Chimborazo, Miriam Morayma (2015)
The research was conducted at the "Angamarca La Vieja" geographical coordinates 01 ° 06' S 95 "S latitude; S and 79 ° 0 '10 "W longitude at an altitude of 1700 m belonging to the Canton Pangua, Cotopaxi Province. With a duration of 75 days of field work, experimental work 40 days and 35 days of establishment of the trial. Consciousness, black Boca, Peruvian White, Butter, Calima and Witness (Canary) to this a design randomized complete block with four replications and a total of 120 experimental plants used: bean varieties were evaluated….